The Influence of Self Confidence on Social Anxiety Among Upper Secondary Students MAN 3 Banyumas - Muzaimah, Laila Khansa’; Almala, Aftiy Diya (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2025)
This study investigates the influence of self-confidence on social anxiety among upper secondary students, with a primary focus on learners at MAN 3 Banyumas. Employing a quantitative correlational design, data were collected from 100 students selected through random sampling using validated and reliable Likert-scale questionnaires measuring self-confidence and social anxiety. The data were analyzed through a series of prerequisite tests followed by simple linear regression to determine the strength and significance of the relationship between the two variables. The results indicate that self-confidence has a statistically significant relationship with social anxiety, although the magnitude of its contribution is relatively low, accounting for a modest proportion of variance in students’ social anxiety levels. These findings suggest that self-confidence remains a relevant psychological factor in adolescent social development, even though it operates alongside other unmeasured influences. From an applied perspective, the results highlight the potential value of confidence-building interventions within school settings to support students’ social and emotional functioning. Nevertheless, the cross-sectional design and the focus on a single institutional context limit causal interpretation and generalizability. Future research is recommended to employ longitudinal or experimental approaches and to incorporate additional psychosocial variables to obtain a more comprehensive understanding of factors shaping social anxiety among adolescents.